Pengaruh Beban Kerja, Motivasi Kerja, Dan Kompensasi Kerja Terhadap Produktivitas Karyawan (Studi Kasus pada Karyawan CV. Maju Djaya Beton) - Chazanah, Dinda Wahyu Nur; Khalikussabir, Khalikussabir; Suharto, M. Khoirul Anwarudin Broto (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research aims to analyze the effect of workload, work motivation, and work compensation on employee productivity at CV. Maju Djaya Beton, Singosari, Malang. Using a quantitative approach method with the distribution of questionnaires to all employees totaling 32 respondents using saturated sampling technique (census). The variables studied, workload, work motivation, and work compensation, are among the important factors in measuring employee productivity levels. The results of this study indicate that simultaneously, workload, work motivation, and work compensation have an effect on employee productivity. The workload is known to have a negative and insignificant effect on work motivation, while work compensation partially affects employee productivity. This study suggests that companies need to pay attention to the balance of workload, improve motivation, and provide appropriate compensation to increase employee productivity. Keywords: Workload, Work Motivation, Work Compensation, Employee Productivity.